Russian Hotel Chains: Formation and Development Trends - KULGACHEV, Ivan P.; KOSOLAPOV, Alexander B.; SAVINKINA, Larisa A.; DRACHEVA, Elena L.; BABAKHANOVA, Irina B. (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).07, 2020)
The hotel business in Russia is developing at an accelerated pace. The increase in the number of collective accommodation facilities and their incomes is associated with a stable economic and socio-political situation in the country, with effective state regulation of the tourism sector and the formation of a country's image favorable for tourism and travel. Foreign hotel chains are actively introducing themselves into the hotel services market in Russia. At the same time, Russian hotel chains are being created, intensifying their activities not only in the Russian, but also in the international hospitality industry market.